Karakteristik Demografi Terkait Komplikasi Pada Penderita Hipertensi di Kota Semarang - Annisa Putri Fatmasari; Widya Hary Cahyati (Dian Nuswantoro Semarang, 2021)
Objective and Background: The increase in the prevalence of hypertension shows that hypertension is a top priority for health problems, the higher the hypertension rate the higher the risk of complications. In 2020, Puskesmas Bandarharjo became the health facility with the highest number of hypertension cases, namely 12,692 with DM complications by 45%, complications from heart disease 30%, and stroke 25%. This study aims to determine the risk factors for the incidence of complications in hypertensive patients in the work area of the Bandarharjo Public Health Center, Semarang City. This study focuses on risk factors for demographic characteristics such as age, gender, heredity, and level of community knowledge of the incidence of complications. Methods: This research is analytic observational with a case-control approach design. This study used a purposive sampling technique with a sample size of 31 cases and 31 controls. Meanwhile, data analysis was carried out by univariate, bivariate using the chi-square test, and multivariate analysis with the help of SPPS version 24. The Results: showed that there was a relationship between age (p = 0.000), family history / descent (p = 0.005), education level (p = 0.011. There was no relationship between gender (p = 0.610). Conclusions: the need to increase health promotion in the context of controlling complications of hypertension patients in the Bandarharjo Community Health Center working area for the surrounding community.